CLASSROOM INTERACTION IN ENGLISH LESSON BASED ON FLANDER’S INTERACTION CATEGORIES (FIAC) - Elfridayani Purba; Amrin Saragih; Siti Aisyah Ginting (Universitas Negeri Medan, 2017)
This study focuces on analyzing the process of classroom interaction through Flanders Interaction Analysis Category (FIAC) model. The objective was to describe how the teacher and students use the categories of classroom interaction in English class by using Flanders Interaction Analysis Category (FIAC) model. The data was found based on the data transcription. The source of the data was the utterances between English teacher and 7th grade students at SMP N 1 SEIBAMBAN. The instruments for data collection were observation, video recording, and note talking. The data analysis applied descriptive qualitative research. It was found that the total percentage each categories classroom interaction were accepts feelings (0.57%), praise and encourages (1.34%), accepts or uses the ideas of the students (0.19%), asks questions (13.74%), lecturing (7.06%), giving directions (30.9%), criticizing or justifying authority (3.91%), students talk-response (28.81%), students talk-initiation (0.29%), and silence or confusion (13.17%). It showed that students participated in the interaction process. Keywords: Teacher Talk, Students Talk, Flanders Interaction Analysis Categories (FIAC) model.